Ayurveda-based Botanicals as Therapeutic Adjuvants in Paclitaxel-induced Myelosuppression - Saggam, Akash; Kale, Prathamesh; Shengule, Sushant; Patil, Dada; Gautam, Manish; Tillu, Girish; Joshi, Kalpana; Gairola, Sunil; Patwardhan, Bhushan (Frontiers in Pharmacology, 2022)
Chemotherapy-induced myelosuppression is one of the major challenges in cancer treatment. Ayurveda-based immunomodulatory botanicals Asparagus racemosus Willd. (AR/Shatavari) and Withania somnifera (L.) Dunal (WS/Ashwagandha) have potential role to manage myelosuppression. We have developed a method to study the effects of AR and WS as therapeutic adjuvants to counter paclitaxel (PTX)-induced myelosuppression. Sixty female BALB/c mice were divided into six groups – vehicle control (VC), PTX alone, PTX with aqueous and hydroalcoholic extracts of AR (ARA, ARH) and WS (WSA, WSH). The myelosuppression was induced in mice by intraperitoneal administration of PTX at 25 mg/kg dose for three consecutive days. The extracts were orally administered with a dose of 100 mg/kg for 15 days prior to the induction with PTX administration. The mice were observed daily for morbidity parameters and were bled from retro-orbital plexus after two days of PTX dosing. The morbidity parameters simulate clinical adverse effects of PTX that include activity (extreme tiredness due to fatigue), behavior (numbness and weakness due to peripheral neuropathy), body posture (pain in muscles and joints), fur aspect and huddling (hair loss). The collected samples were used for blood cell count analysis and cytokine profiling using Bio-Plex assay. The PTX alone group showed a reduction in total leukocyte and neutrophil counts (4800 ± 606; 893 ± 82) when compared with a VC group (9183 ± 1043; 1612 ± 100) respectively. Pre-administration of ARA, ARH, WSA, and WSH extracts normalized leukocyte counts (10000 ± 707; 9166 ± 1076; 10333 ± 1189; 9066 ± 697) and neutrophil counts (1482 ± 61; 1251 ± 71; 1467 ± 121; 1219 ± 134) respectively. Additionally, higher morbidity score in PTX group (7.4 ± 0.7) was significantly restricted by ARA (4.8 ± 1.1), ARH (5.1 ± 0.6), WSA (4.5 ± 0.7), and WSH (5 ± 0.8). (Data represented in mean ± SD). The extracts also significantly modulated 20 cytokines to evade PTX-induced leukopenia, neutropenia, and morbidity. The AR and WS extracts significantly prevented PTX-induced myelosuppression (p<0.0001) and morbidity signs (p<0.05) by modulating associated cytokines. The results indicate AR and WS as therapeutic adjuvants in cancer management.